Trapezoid bioequivalence: A rational bioavailability evaluation approach on account of the pharmaceutical‐driven balance of population average and variability - Sara Soufsaf; Fahima Nekka; Jun Li (Wiley, 2022)
Abstract Among the current approaches for the analysis of bioequivalence, the average bioequivalence (ABE) is limited only to the mean bioavailability, whereas the population bioequivalence (PBE) criterion aggregates both mean and variance in a general comparison formula. However, a rational bioequivalence criterion capable of judging specific drug considerations is always still preferred. As an alternative approach, we introduce an aggregate criterion, namely, the trapezoid bioequivalence (TBE), which includes the consideration of both mean and variance of the bioavailability and adapted weighting of a drug's therapeutic properties. We first applied our method to specific simulated scenarios to compare the strengths and weaknesses of current bioequivalence approaches and demonstrate the improvements brought by TBE. As well, the impact of sample size and variability on ABE, PBE, and TBE are assessed using a population pharmacokinetic model of methylphenidate. Our results indicate that TBE inherits the advantages of both ABE and PBE while greatly reducing their inadequacies. Through simulations with population pharmacokinetic models of specific scenarios, we confirm that (1) TBE does not encounter the overly permissiveness issue of PBE, (2) TBE respects the hierarchy to ABE (TBE => ABE), and (3) TBE assesses bioequivalence with a restriction on σT2‐σR2 without an increase to type 2 errors. The clinically inspired simulations demonstrate TBE's superiority in a realistic context and its potential usefulness in practice. Moreover, the parameter choice in TBE may be adapted according to the specific context of a drug's pharmacological and pharmacodynamic properties.